Effect of religious beliefs on the smoking behaviour of university students: quantitative findings from Malaysia - Elkalmi, Ramadan Mohamed Mahmod; Alkoudmani, Ramez M.; Elsayed, Tarek Mohamed Ali; Ahmad, Akram; Khan, Muhammad Umair (Springer, 2015)
The Malaysian ofﬁcial Islamic authorities have issued a ‘‘fatwa’’ (Islamic ruling) regarding smoking practice which prohibits Muslims from smoking because of its potential harm to health. Since the prevalence of smoking among Malaysian students is high, this study was designed to explore the perceptions and opinions of Malaysian Muslim students towards smoking in International Islamic University of Malaysia. A prospective, cross-sectional study was conducted among School of Science students in International Islamic University Malaysia. Convenience sampling approach was used to recruit 323 students based on sample size calculation. A content- and face-validated questionnaire was used to collect the data from the participants. Non-smokers highly supported the fatwa on smoking forbiddance than smokers (94 vs 64.3 %, p = 0.001). A signiﬁcant proportion of non-smokers believed that Islam prohibits smoking because of its potential harm (94.9 vs 71.4 %, p = 0.001). Majority of smokers agreed that addiction is the main barrier towards smoking cessation (78.6 vs 61.5 %, p = 0.019). The results showed positive inﬂuences of Islamic beliefs on the non-smokers. Further studies are required to validate these ﬁndings by surveying other universities of Malaysia.